Humanized antibody neutralizing 2009 pandemic H1N1 virus. Issue 12 (8th August 2014) - Shembekar, Nachiket; Mallajosyula, Vamsee V Aditya; Chaudhary, Piyush; Upadhyay, Vaibhav; Varadarajan, Raghavan; Gupta, Satish Kumar
Abstract The 2009 pandemic H1N1 S‐OIV (swine origin influenza A virus) caused noticeable morbidity and mortality worldwide. In addition to vaccine and antiviral drug therapy, the use of influenza virus neutralizing monoclonal antibodies (MAbs) for treatment purposes is a viable alternative. We previously reported the isolation of a high affinity, potently neutralizing murine MAb MA2077 against 2009 pandemic H1N1 virus. We describe here the humanization of MA2077 and its expression in a mammalian cell line. Six complementarity‐determining regions (CDRs) of MA2077 were grafted onto the human germline variable regions; along with six and eight back mutations in the framework of heavy and light chains, respectively, pertaining to the vernier zone and interchain packing residues to promote favorable CDR conformation and facilitate antigen binding. The full length humanized antibody, 2077Hu2, expressed in CHO‐K1 cells, showed high affinity to hemagglutinin protein (KD = 0.75 ± 0.32 nM) and potent neutralization of pandemic H1N1 virus (IC50 = 0.17 μg/mL), with marginally higher IC50 as compared to MA2077 (0.08 μg/mL). In addition, 2077Hu2 also retained the epitope specificity for the "Sa" antigenic site on pandemic HA. To the best of our knowledge, this is the first report of a humanized neutralizing antibody against pandemic H1N1 virus.